Impact of the Economic Justification of Punishment on the System of Certain Crimes - Papoyan, Hrayr; Vanyan, Venera («Տնտեսագետ» հրատ․)
Gary Becker's theory («Crime and Punishment: An Economic Approach») was studied and presented in the article. In this theory, Gary Becker presents the criminal as an individual who evaluates his income and costs, his time, and his risk differently. Based on this, he divides criminals into two categories: • risk-prone criminals, for whom the likelihood of detection plays a huge role, • risk-averse criminals, for whom the severity of punishment is of paramount importance. Based on this, the articles on theft in the Criminal Code of the RA and foreign countries were studied. We also studied the statistics of theft and crime and statistics of crime detection. In addition, to understand how the severity of punishment affects the theft rate in the RA and foreign countries, we introduced the economic index of the severity and the weighted economic index of punishment. We found out that the economic index of the severity of punishment does not have an impact on the crime rate. However, in the RA the weighted economic index of punishment has a more significant impact on criminal intent of criminals, which reduces the number of theft cases. Also, the main risk factor for criminals in the RA and foreign countries is the likelihood of crime detection, which is discussed in Becker’s theory.
Keywords: System of certain crimes